Early epileptiform EEG activity in infants with tuberous sclerosis complex predicts epilepsy and neurodevelopmental outcomes. (29th March 2021) - De Ridder, Jessie; Verhelle, Birgit; Vervisch, Jan; Lemmens, Katrien; Kotulska, Katarzyna; Moavero, Romina; Curatolo, Paolo; Weschke, Bernhard; Riney, Kate; Feucht, Martha; Krsek, Pavel; Nabbout, Rima; et al.
Summary: Objective: To study the association between timing and characteristics of the first electroencephalography (EEG) with epileptiform discharges (ED‐EEG) and epilepsy and neurodevelopment at 24 months in infants with tuberous sclerosis complex (TSC). Methods: Patients enrolled in the prospective Epileptogenesis in a genetic model of epilepsy – Tuberous sclerosis complex (EPISTOP) trial, had serial EEG monitoring until the age of 24 months. The timing and characteristics of the first ED‐EEG were studied in relation to clinical outcome. Epilepsy‐related outcomes were analyzed separately in a conventionally followed group (initiation of vigabatrin after seizure onset) and a preventive group (initiation of vigabatrin before seizures, but after appearance of interictal epileptiform discharges [IEDs]). Results: Eighty‐three infants with TSC were enrolled at a median age of 28 days (interquartile range [IQR] 14–54). Seventy‐nine of 83 patients (95%) developed epileptiform discharges at a median age of 77 days (IQR 23–111). Patients with a pathogenic TSC2 variant were significantly younger ( P ‐value .009) at first ED‐EEG and more frequently had multifocal IED ( P ‐value .042) than patients with a pathogenic TSC1 variant. A younger age at first ED‐EEG was significantly associated with lower cognitive ( P ‐value .010), language ( P ‐value .001), and motor ( P ‐value .013) developmental quotients at 24 months. In the conventional group, 48 of 60 developed seizures. In this group, the presence of focal slowing on the first ED‐EEG was predictive of earlier seizure onset ( P ‐value .030). Earlier recording of epileptiform discharges ( P ‐value .019), especially when multifocal ( P ‐value .026) was associated with higher risk of drug‐resistant epilepsy. In the preventive group, timing, distribution of IED, or focal slowing, was not associated with the epilepsy outcomes. However, when multifocal IEDs were present on the first ED‐EEG, preventive treatment delayed the onset of seizures significantly ( P ‐value <.001). Significance: Early EEG findings help to identify TSC infants at risk of severe epilepsy and neurodevelopmental delay and those who may benefit from preventive treatment with vigabatrin.